2014
DOI: 10.1007/s11356-014-3539-7
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal arrangement of anodes of microbial fuel cells enhances remediation of petroleum hydrocarbon-contaminated soil

Abstract: With the aim of in situ bioremediation of soil contaminated by hydrocarbons, anodes arranged with two different ways (horizontal or vertical) were compared in microbial fuel cells (MFCs). Charge outputs as high as 833 and 762C were achieved in reactors with anodes horizontally arranged (HA) and vertically arranged (VA). Up to 12.5 % of the total petroleum hydrocarbon (TPH) was removed in HA after 135 days, which was 50.6 % higher than that in VA (8.3 %) and 95.3 % higher than that in the disconnected control (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 30 publications
0
28
1
Order By: Relevance
“…2). It is probably because low molecular weight PAHs, containing two-to three-ringed PAHs were less toxic to microbes in the soil and can serve as a carbon source involved in the microbial metabolisms and accumulated more in the sediment8. Also high molecular weight PAHs, containing four-to six-ringed PAHs were hard to be decomposed by microbes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2). It is probably because low molecular weight PAHs, containing two-to three-ringed PAHs were less toxic to microbes in the soil and can serve as a carbon source involved in the microbial metabolisms and accumulated more in the sediment8. Also high molecular weight PAHs, containing four-to six-ringed PAHs were hard to be decomposed by microbes.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies also suggested that Microbial Fuel Cells (MFCs) may be used for enhancing biodegradation of contaminants in anoxic environments by providing an inexhaustible source of terminal electron acceptors to a polluted environment89. Based on microbe–electrode interactions, various systems are being developed with time to not only remove organics, but also for the production and recovery of value-added products from substrates10.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The removal of hydrocarbons in soil is correlated with bio-current generated by exoelectrogenes (Li et al, 2014b;Lu et al, 2014a;Zhang et al, 2014). Using MFCs to remediate sediment contaminated by hydrocarbons, the degradation rate increased by up to 12 times from 2% to 24% in 66 d. However, according to the low power density reported previously (an average of 37 mW m À3 ), the system heavily suffered from very high internal resistance of $4 kX, mainly attributed to the high Ohmic resistance as a result of low conductivity in soil (Morris and Jin, 2012).…”
Section: Introductionmentioning
confidence: 99%